Ibn Rashiq’s Al-Omdah and Al-Nahshali’s Almumte’ between Originality and Influence: A Comparative Study - shdouh, Ala Mohammad (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to thoroughly explore Al-Omdah in the Beauties of Poetry: Its Literature and Criticism by Ibn Rashiq Al-Qayrawani and Almumte’ by Abd Al-Karim Al-Nahshali. It aims to compare and contrast the two books and to examine forms of influence in the student’s work. The most important research question that this study aspires to answer is: Does what the two authors’ works have in common represent influence or literal copying? Methods: The study relies on the investigative method, pointing out multiple points of similarity between the two books. It also adopts an analytical and comparative approach through which the texts are analyzed and percentages of similarities and differences as well as additions and omissions are estimated and justified. Moreover, some historical and social facts that pertain to both authors are used as important factors in achieving the study’s results. Results: The study proves that Ibn Rashiq and his student Al-Nahshali shared many social and historical circumstances, which justifies the mutual influence between them. It also demonstrates that Ibn Rashiq, as he states in the introduction to his book, quoted many critical and other issues from several critics, especially Al-Nahshali. Ibn Rashiq’s literary borrowing takes a variety of forms; the most dangerous of which is copying. Conclusion: The study reveals that Ibn Rashiq’s several literary borrowings from his teacher without acknowledging his source does not undermine the literary value of his works or render him a plagiarist. However, the study perceives the importance of referring to this kind of borrowing when it comes to a prominent Arab critic like Ibn Rashiq.